Anak Tak Sah Taraf Dari Perspektif Syariah Dan Perundangan Islam Di Malaysia - Hj Ismail, Paizah (Jurnal Fiqh, 2017)
Illegitimate child generally means a child born to parents who are not legally married. However, scholars have different opinions on a number of associated conditions. This article aims to analyse the different opinions among scholars and the stand of fatwa in the issue of illegitimate child. This article also analyses Islamic Family Law in Malaysia and its implications for illegitimate child?s position in the family particularly in determining the name and inheritance problem. The library research focuses on reanalysing the opinions of classical jurists by taking into account the contemporary context of illegitimate child issues. One of the conclusions of this article is that, to be regarded as a legitimate child by the current Muslim community in Malaysia , the child has to be born as a result of a valid marriage in the eyes of the religion and the Islamic family law of the state.